The interconnected multi-cloud: the future of digital security. Issue 5 (May 2017) - Sony, Sachin
Abstract : Cloud-based solutions are now being adopted by businesses at a truly astonishing rate. According to Gartner, the global public cloud services market broke the $200bn mark in 2016, driven largely by growth in the infrastructure as a service (IaaS) and software as a service (SaaS) segments. And while political uncertainty in the US and Europe is expected to restrain IT spending to a certain degree, the market is still expected to further grow in 2017.